Delegating responsibility : international cooperation on migration in the European Union - Micinski, Nicholas R. (University of Michigan Press, 2022)
Delegating Responsibility explores the politics of migration in the European Union and explains how and why the EU responded to the 2015-17 refugee crisis. Based on 86 interviews and fieldwork in Greece and Italy, Nicholas R. Micinski puts forward a new theory of international cooperation on international migration. States approach migration policies in many ways--such as coordination, collaboration, subcontracting, and unilateralism--but which way they choose is based on the migration state capacity and credible partners on the ground. Micinski traces the evolution of EU migration management, like border security and asylum policies, over the last fifty years and shows how EU officials used "crises" as political leverage to further Europeanize migration governance. In two in-depth cases studies, he explores these themes to explain how Italy and Greece responded to the most recent refugee crisis. He concludes with a discussion of policy recommendations regarding the current situation and long-term aspirations for migration management in the EU. This book is an excellent introduction to the politics of the EU, migration and refugee policy, and humanitarianism and presents original data and findings from the 2015-17 refugee crisis